Is the Control Environment a Basis for Customised Risk Management Initiatives in South African Small, Medium and Micro Enterprises? - Juan-Pierré BRUWER; Luyolo SIWANGAZA (Expert Journal of Business and Management, 2016)
Before the official recognition of Small, Medium and Micro Enterprises (SMMEs) in South Africa during the mid-1990s, these business entities have been key players in the stimulation of the national economy. Albeit their socio-economic value added, prior research shows that the sustainability of these business are among the worst in the world, since approximately 70% of South African SMMEs fail within their first three years of existence. This dispensation is often blamed on inter alia, their inadequate management of economic factors which, in turn, cultivates risks. Notwithstanding the fact that most South African SMMEs make use of customised risk management initiatives, previous research shows that these initiatives are not deemed as adequate and/or effective to mitigate risks. Since the manner in which risks are managed are strongly dependent on the attitude and awareness of its management surrounding internal control (control environment), this study focused on investigating whether the control environment was used as foundation to implement their customised risk management initiatives. Empirical research was conducted whereby primary quantitative data were collected from respondents through the deployment of a questionnaire, through means of non-probability sampling methods. The results showed that though the control environments of South African SMMEs were regarded as good, they were not used as foundation by South African SMMEs to implement their customised risk management initiatives.